Biotic Interferences and other Problems Faced by the Elephants in the most Crucial Corridors of Eastern Ghats - Srivastava, Rajiv K. (Indian Forester, 2002)
Elephant (Elephas maximus), the most important wild animal found in the Eastern Ghats facing mounting problems by the way of biotic interference. In this paper biotic interference, other problems and their effects in two most crucial corridors (Vethalakkal-Badanavadi, RF and Vethalakkal-Marandahalli) of elephants in the Eastern Ghats have been studied in detail. These corridors have never been studied so far, nor highlighted in the past. This is the first time the corridors rout were studied in details. The area is situated in and around Hogenakkal at the border of Tamil Nadu and Karnataka. Adverse impact faced by the elephants in these corridors of monoculture, fragmentation and poaching have also been studied.